1983
DOI: 10.1093/infdis/148.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Posttransfusion Non-A, Non-B Hepatitis: Physicochemical Properties of Two Distinct Agents

Abstract: Two separate and distinct episodes of non-A, non-B hepatitis were induced in each of two chimpanzees by two inocula: one containing a chloroform-resistant agent and the other containing a chloroform-sensitive agent. Both agents were recovered from liver tissue and plasma obtained from a single chimpanzee during the acute and chronic phases of infection with a factor VIII concentrate, respectively. The chloroform-resistant agent did not cause unique changes in hepatocytes; in contrast, the chloroform-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
3

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(64 citation statements)
references
References 25 publications
5
56
0
3
Order By: Relevance
“…These characteristics, as well as the gene organization of HCV, are consistent with the theory that at least one of the causative agents of post-transfusion non-A, non-B hepatitis is a small enveloped virus, such as a togavirus or flavivirus (Bradley et al, 1983). This assumption was derived mainly from chimpanzee infection experiments showing that the infectious agent has an envelope 0001-0140 © 1991 SGM containing lipid and is less than 80 nm in diameter (Bradley et al, 1983(Bradley et al, , 1985Feinstone et al, 1983). It has been shown also that the buoyant density of the infectious particles in sucrose is 1-09 to 1.11 g/ml (D. W. Bradley, personal communication).…”
Section: Laboratory Of Hepatitis Viruses 11 Department Of Enterovirsupporting
confidence: 83%
See 1 more Smart Citation
“…These characteristics, as well as the gene organization of HCV, are consistent with the theory that at least one of the causative agents of post-transfusion non-A, non-B hepatitis is a small enveloped virus, such as a togavirus or flavivirus (Bradley et al, 1983). This assumption was derived mainly from chimpanzee infection experiments showing that the infectious agent has an envelope 0001-0140 © 1991 SGM containing lipid and is less than 80 nm in diameter (Bradley et al, 1983(Bradley et al, , 1985Feinstone et al, 1983). It has been shown also that the buoyant density of the infectious particles in sucrose is 1-09 to 1.11 g/ml (D. W. Bradley, personal communication).…”
Section: Laboratory Of Hepatitis Viruses 11 Department Of Enterovirsupporting
confidence: 83%
“…The nucleotide and deduced aa sequences of the genomes of different isolates have shown that HCV is distantly related to flaviviruses and pestiviruses Miller & Purcell, 1990;Takeuchi et al, 1990;Kato et al, 1990;Takamizawa et al, 1991 ;Choo et al, 1991 ;Han et al, 1991). These characteristics, as well as the gene organization of HCV, are consistent with the theory that at least one of the causative agents of post-transfusion non-A, non-B hepatitis is a small enveloped virus, such as a togavirus or flavivirus (Bradley et al, 1983). This assumption was derived mainly from chimpanzee infection experiments showing that the infectious agent has an envelope 0001-0140 © 1991 SGM containing lipid and is less than 80 nm in diameter (Bradley et al, 1983(Bradley et al, , 1985Feinstone et al, 1983).…”
Section: Laboratory Of Hepatitis Viruses 11 Department Of Enterovirsupporting
confidence: 59%
“…In comparison, it has been estimated that the number of Dane particles in HBV carriers seropositive for hepatitis B e antigen is more than 10 l° per ml of plasma with chimpanzee infectious titres of 108 to 109 per ml (Shikata et al, 1977). The above calculations for HCV are consistent with chimpanzee infectivity studies of human plasma, where infectivity titres of about 103/ml were usually observed (Bradley et al,~ 1983).…”
Section: Discussionsupporting
confidence: 58%
“…In the data presented here, the total number of persons with hemophilia A who had intrinsic liver disease listed as a cause of death increased 3-fold from 1979-1982 to 1995-1998; the greatest numbers contributing to this increase also have HIV-related disease. This may, in part, reflect the sequelae of exposures to HBV and HCV, as well as other non-A, non-B hepatitis agents [53,54]. Levels of serum aspartate aminotransferase and HCV RNA are much higher among multitransfused persons with hemophilia A who are HIV-positive than among those who are HIV-negative, suggesting that HIV infection promotes increased HCV replication [55].…”
Section: Impact Of Hepatitismentioning
confidence: 99%